Efficient Realizations of CNOT gates in IBM's Quantum Computers - Almeida, Alexandre A. A. de [UNESP]; Dueck, Gerhard W.; Silva, Alexandre C. R. da [UNESP]; Jose, B. A.; Mathew, J. (Ieee, 2018)
IBM's quantum computers implement gates from Clifford+T gate library. All single qubit gates are implemented, but only a subset of the possible CNOT are provided. It is well known that the functionally of the missing gates can be achieved by a sequence of gates. The sequence of gates is based on SWAP gates. Up to seven elementary gates are required to implement a SWAP gate. In this paper we show how the same effect can be achieved with fewer gates. To show the potential of the proposed transformations, an example is presented where a reduction of 44% in the gate count and a 26% reduction in the number of levels for IBM's QX5 computer is achieved. An algorithm that is considered state of the art, is used for the comparison.